المشكلات السلوكية في الوسط المدرسي لدى تلاميذ مرحلة المتوسط من وجهة نظر المشرفين التربويين - حمويه اسماعيل; سعادة رشيد (University of Eloued جامعة الوادي, 2024)
هدفت الدراسة الحالية إلى التعرف على نسبة انتشار المشكلات السلوكية (السلوك الانعزالي، سلوك العنف، سلوك تقدير الذات) لـدى تلاميذ المرحلة المتوسط في ولاية الوادي من وجهة نظر مشرفي التربية، وهل يختلف عند أفراد العينة باختلاف متغيري المستوى الدراسي والنوع الاجتماعي. وتكونت عينة من (78) تلميذا منهم (60) تلميذا و (18) تلميذة، تم اختيارهم بالطريقة العشوائية، ولتحقيق أهداف الدراسة قام الباحث باستعمال أداة مكونة من (39) فقرة لقياس نسبة انتشار المشكلات السلوكية لدى تلاميذ المرحلة المتوسط، وتم التأكد من دلالات صدقها وثباتها، وأشارت النتائج ما يلي: 1-قدرت نسبة الانتشار المسجلة على لوحة الانتشار بـ 92 بالمائة ، للمشكلات السلوكية (السلوك الانعزالي، سلوك العنف، سلوك تقدير الذات ) لـدى تلاميذ المرحلة المتوسط. 2- نسبة الانتشار المسجلة لسلوك الانعزالي مع المشكلات السلوكية قدرت قيمة بـــــ (0.96). 3- نسبة الانتشار المسجلة سلوك العنف مع المشكلات السلوكية قدرت قيمة بـــــ (0.30). 4- نسبة الانتشار المسجلة سلوك تقدير الذات مع المشكلات السلوكية قدرت قيمة بـــــ (0.17). Abstract: This study aims to identify the prevalence of behavioral problems in the school environment among middle school pupils in Eloued City from school counselor’s view, and does it differ among the sample members according to the variables of educational level and gender. A sample consisted of 78 pupils: 60 male and 18 female, selected randomly. To achieve the study's objectives, the researcher used a tool consisting of 39-paragraphs to measure the prevalence of behavioral problems among middle school pupils, The result’s validity and reliability were confirmed, and the results indicated the following: 1. The prevalence rate recorded on the spreadsheet was estimated at 92% for behavioral problems (social isolation behavior, violent behavior, and self-esteem behavior) among middle school pupils. 2. The prevalence rate of social isolation behavior with behavioral problems, was set at 0.96. 3. The recorded prevalence rate of violent behavior with behavioral problems was 0.30. 4. The recorded prevalence of self-esteem behavior with behavioral problems was set at 0.17.
دراسة ميدانية بمدينة الوادي
Keywords: المشكلة; السلوك; المشكلات السلوكية; مرحلة التعليم المتوسط; The problem; Behavior; Behavioral problems; Middle schoo